Isolasi dan Karakterisasi Fungi Selulolitik dari Tanah Gambut Cagar Biosfer Giam Siak Kecil-Bukit Batu, Riau - Devitria, Rosa; Sepriyani, Harni (Jurnal Akademika Kimia, 2018)
Fungi is primary microorganism which produced cellulase enzyme. Cellulase was catalyzed cellulose from plants or organic waste in enzymatic reaction to be glucose, cellobiose and short polysaccharide. Cellulolytic fungi were isolated from Giam Siak Kecil-Bukit Batu (GSKBB) biosphere reserve. GSKBB is a natural peat swamp forest, with a peat bed reaching up to 9.2 m. Peat swamp forest is a potential source for new species of fungi which produced cellulase in low pH and very good activity because peat swamp forest had been many cellulose and acid pH. Fungi strain was assigned as RH01 at Aspergillus for genus based on microscopy analysis. Index cellulolytic of RH01 was 2.31 and cellulase activity had values of 0.0125 U/mL.Â